Transformasi Usaha Mikro Kecil dan Menengah: Menuju Bisnis Kreatif dan Inovatif - Pramesworo, Septo; Yustisia, Natali; Evi, Tiolina (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia play an important role in the community's economy. MSMEs must carry out creative and innovative efforts to improve their business and encourage economic growth. However, MSMEs often face challenges in facing increasingly fierce competition and changing market trends. In the ever-growing digital era, developing digitalization of MSME businesses has become an urgent need to increase their competitiveness. The development of digitalization of MSME businesses opens up great opportunities for business growth and development. Apart from digitalization, MSMEs should be creative and innovative, either by collaborating, inviting other parties, or using digital technology and online platforms, MSMEs can expand their market reach and reach potential consumers in various regions. However, the development of digitalization of MSME businesses also faces several challenges. Keywords: Creativity, Innovation, Digital Technology, MSMEs